ANALISIS KINERJA SIMPANG EMPAT TAK BERSINYAL PERSIMPANGAN TANJUNG PATI KABUPATEN 50 KOTA - Fauzan Azima; Helga Yermadona; Ishak Ishak (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Congestion often occurs at several crossroads in the district. Therefore, efficient and optimal handling is needed, as well as planning for Traffic Lights. In this thesis research examines the Performance Analysis of Unsignaled Intersection. The research location is on the West Sumatra-Riau Cross Road, precisely at the Tanjung Pati Intersection, Fifty Cities Regency with 4 intersection arms, namely Tanjung Pati Road, West Sumatra-Riau Road, Lubuak Batingkok Road, and Batu Balang Road. The purpose of this study is to determine the traffic volume and whether it is necessary to reactivate the Traffic Light (Red Light) at the Tanjung Pati Simpang Empat. Data collection was obtained through field surveys. From the results of research and discussion at the Tanjung Pati Intersection, it was found that the degree of saturation (DS) was 1.25 with an average delay of 141 seconds/pcu. So from these calculations we can conclude that at Simpang Empat Tanjung Pati it is necessary to reactivate the Traffic Light to reduce traffic congestion that occurs at certain peak hours. Keywords: Traffic Light, unsignalized intersection, degree of saturation, time delay.